PENENTUAN STRATEGI PRODUCTIVE MAINTENANCE PADA ELECTRIC ARC FURNACE PT ISPAT INDO MELALUI PENDEKATAN INTERNATIONAL SAFETY RATING SYSTEM (ISRS) - Irmawan, Irmawan; Iviana Juniani, Anda; Priyonggo, Projek (Widya Warta, 2012)
ISPATINDO, a steel melting factory with production capacity 3360 tons/day, operates the electric arch furnace (EAF) to transform steel into liquid at Steel Melting Shop (SMS). It is then conveyed to another machine for further process until it becomes billet and wire rope. During its operation, the electric arc furnace once exploded on March 3rd, 2004.The explosion made 13 workers get wounded and even some died. Up to now, EAF components have frequently been damaged and repaired prior to the scheduled replacements.This condition makes index of reliability of EAF decrease significantly. If there’s no action to improve the maintenance strategy, component failure which may cause accident couldhappen. This research used the International Safety Rating System (ISRS) to determine the maintenance strategy on the electric arc furnace machine. ISRS method was used to obtain critical program which would serve as the main input in the preparation of maintenance strategy. With this strategy it was expected that ISRS could increase the effectiveness of production and prevent against the occurrence of occupational accidents, losses onmanagement, equipment, materials and environment.